THE EFFECT OF LEARNING LOSS ON STUDENT’S COGNITIVE DEVELOPMENT DURING PANDEMIC OF COVID-19 - Suroyo, Suroyo; Putra, Bima Maulana; Ibrahim, Bedriati; Yanuar, Yanuar (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
COVID-19 has had an impact on people's lives and a variety of activities. Public health organizations have advocated for preventative policies to limit viral spread, such as stay-at-home orders that closed businesses and schools as well as limited children's learning and regular activities. The purpose of this quantitative study is to gather information and understanding about the research topic. The aim of this study is to offer an overview of the impact of learning loss on cognitive development in Pekanbaru, Indonesia, during the COVID-19 pandemic. The sample technique for this study is simple random sampling, and the sample population for this study is 400 high school students.  The data is a student's Higher Order Thinking Skills (HOTS) and GPA results during the COVID-19 (before lockdown). The impact of lock down during a pandemic forces schools to close for an extended length of time; the result of school closures is learning loss, which reduces students' cognitive and knowledge growth. Online classes are an alternate option for students to improve their academic skills. That lockdown is one of the most severe problems that the repercussions of COVID-19 have on schooling and unprivileged students may be one step behind due to learning loss.